A Multi-Method Behavior Setting Analysis of a Protracted Refugee Camp in Jordan. Issue 4 (May 2022) - Awamleh, Zaid; Hasirci, Deniz
The study draws upon theory and research on behavior settings to understand how the built environment shapes selected aspects of behavior in a protracted refugee camp located in an urban area in Jordan. Over 3 years, the research used a multi-method analysis of behavior settings within a residential space and an assessment of modifications to the home using a pre-post research design. The findings showed that the settings can carry new meanings although the occupants greatly restrict their behaviors to conform to the settings they occupy. The findings also indicated the importance of the psychological dimension, which was undervalued in previous applications of the theory. The methodology used demonstrated that localized problems can be addressed by analyzing the features of the relevant behavior setting to reveal the underlying source of the problem. This will help identify solutions that promote behavioral changes to ameliorate displacement and improve the built environment.